-2x^2-2x+5=x^2-x-(1+x^2)заранее спасибо :)

-2x^2-2x+5=x^2-x-(1+x^2) заранее спасибо :)
Гость
Ответ(ы) на вопрос:
Гость
-2x^2-2x+5=x^2-x-1-x^2 -2x^2-2x+5=-x-1 -2x^2-x+6=0 2x^2+x-6=0 D=1+4*2*6=49 x= (-1 +- 7)/4 x1= 1,5 x2= -2
Гость
[latex]-2 x^{2} -2x+5= x^{2} -x-(1+ x^{2} ) \\ -2 x^{2} -2x+5= x^{2} -x-1- x^{2} \\ -2 x^{2} -2x+5=-x-1 \\ -2 x^{2} -2x+5+x+1=0 \\ -2 x^{2} -x+6=0/*(-1) \\ 2 x^{2} +x-6=0 \\ D=1+48=49 \\ \sqrt{D} =7\\ x_{1} = \frac{-1-7}{4} = \frac{-8}{4} =-2 \\ x_{2} = \frac{-1+7}{4} = \frac{6}{4} = \frac{3}{2} =1 \frac{1}{2} =1 \frac{5}{10} =1.5[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы